PENGARUH VOLATILITAS ARUS KAS DAN KEPEMILIKAN MANAJERIAL TERHADAP PERSISTENSI LABA - DEWI HASTUTININGTYAS, PRASETYANA; WURYANI, ENI (Jurnal Akuntansi AKUNESA, 2019)
This study aimed to know the effect of cash flow volatility and managerial ownership on earnings persistence. The population used is a manufacturing company listed on the Indonesia Stock Exchange. Based on quantitative research methods with a purposive sampling technique, there are 25 companies become a research sample during period 2014-2017. Data analysis method used is multiple linear regression. The results of this research showed that cash flow volatility has no effect on earnings persistence, while the managerial ownership has a positive effect on earnings persistence. Keywords: Cash Flow Volatility, Managerial Ownership, and Earnings Persistence.